EFFECT OF TIRES INFLATION PRESSURE , TILLAGE DEPTH AND FORWARD SPEED ON SOME FIELD PERFORMANCE CRITERIA OF TRACTOR - Mothana A. Al - Jarrah (Mesopotamia Journal of Agriculture)
The research was conducted to investigate the effect of two inflation pressures for the rear tires of tractor 80 and 130 kpa with two plowing depths by using the moldboard plow 15 - 20 and 20 – 25 cm and three different speeds 2.22 , 3.22 and 5.85 km/hr on vertical vibration of driver seat , drawbar power , consumed energy , slippage percentage , tractive efficiency and power lost due to slippage . Split split plot design and randomized complete block design with three replications was used in this experiment . Results showed that the effect of inflation pressure was significant in all studied characteristics except the tractive efficiency , and the relation between the inflation pressure and every one of vertical vibration of driver seat , consumed energy , slippage percentage and power lost due to slippage was extrusive whereas the relation was inversely with drawbar power and tractive efficiency . The effect of plowing depth and forward speed was significant in all studied characteristics .